Beloved Bad Boys - De Blasio, Antonella (E|C, 2020)
Classical antiheroes are fragile, weak, envious, lack intelligence and physical prowess, but their moral flaws and failures are usually overlooked by readers because they are attributed to past mistakes or counterbalanced by a deeper virtue (Eaton 2010; 2012). The rough heroes, on the other hand, are evil characters with heroic traits, whose defects are always of a moral nature and do not represent an isolated aspect of their personality, but are an integral part of it, unlike what happens for antiheroes, who usually have a hidden positive. In other words, they are morally corrupt individuals, with very few traits of humanity that do not save them from being judged in a completely negative way.